2003
DOI: 10.1104/pp.103.022228
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Cyclic GMP Are Messengers in the Indole Acetic Acid-Induced Adventitious Rooting Process

Abstract: This report describes part of the signaling pathway and some of the molecules involved in the auxin-induced adventitious root formation in cucumber (Cucumis sativus). Previous results showed that nitric oxide (NO) mediates the auxin response during adventitious root formation (Pagnussat et al., 2002). To determine the order of action of indole acetic acid (IAA) and NO within the signal transduction pathway and to elucidate the target molecules that are downstream of NO action, cucumber hypocotyl cuttings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
245
1
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 355 publications
(276 citation statements)
references
References 40 publications
16
245
1
14
Order By: Relevance
“…Consequently, NO activates signalling pathways, which results in changes of gene expression, through intermediate cellular messengers. Several lines of evidence indicate that cGMP acts downstream of NO signalling (Durner, Wendehenne & Klessig 1998;García-Mata et al 2003;Neill, Desikan & Hancock 2003;Pagnussat, Lanteri & Lamattina 2003). Interestingly, it was recently reported that cGMP is required for the NO-dependent expression of genes involved in the flavonoid biosynthetic pathway (Suita et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, NO activates signalling pathways, which results in changes of gene expression, through intermediate cellular messengers. Several lines of evidence indicate that cGMP acts downstream of NO signalling (Durner, Wendehenne & Klessig 1998;García-Mata et al 2003;Neill, Desikan & Hancock 2003;Pagnussat, Lanteri & Lamattina 2003). Interestingly, it was recently reported that cGMP is required for the NO-dependent expression of genes involved in the flavonoid biosynthetic pathway (Suita et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…cGMP is an intracellular messenger downstream of NO action and is synthesized in response to auxin stimulation (Pagnussat et al, 2003). Consequently, we assessed the potential involvement of cGMP in 3-O-C10-HL-induced adventitious root formation.…”
Section: Involvement Of Cgmp In 3-o-c10-hl-induced Adventitious Rootmentioning
confidence: 99%
“…Adventitious roots are derived primarily from plant stems and are essential for plant adaptation to environmental stress; studying the adventitious root formation is also significant for both fundamental and applied plant biology. The phytohormone auxin plays an essential role in stimulating adventitious root formation (Pagnussat et al, 2003(Pagnussat et al, , 2004. Significant progress has been made to elucidate the molecular mechanism of auxin action via the auxin/ indole-3-acetic acid (Aux/IAA) and auxin-response factor (ARF) gene families.…”
mentioning
confidence: 99%
See 2 more Smart Citations